Our experience of resection of a giant akinetic aneurysm of the left ventricle (with the threat of a rupture of the wall) with left ventricular plasty and aorto-coronary bypass grafting (case from practice) - Djumaniyazov, A. A. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The technique of left ventricular plasty by a two-tiered seam, with simultaneous elimination of the septal part of the dome of the aneurysm head by corrugating it with a lower-tiered suture, is an effective method of plasty of the left ventricle after a resection of medium and large left ventricular aneurysms. Our goal is introduction of the practice of the center of the technique of left ventricular plastic surgery by a double-tiered seam, with simultaneous elimination of the septal part of the dome of the aneurysm head by corrugating it with a lower-tiered seam developed at the National Institute of Cardiovascular Surgery named after N. M. Amosov. Material and methods. Patient Yu. J., 57 years old, twice suffered a myocardial infarction in 2012 and 2017. The patient underwent coronaroventriculography, which revealed multiple lesions of the coronary arteries of the heart. The operation was performed: aortocoronary bypass, left ventricular aneurysm resection, LV thrombectomy, LV endventriculoplasty with plication of the interventricular septum in conditions of artificial blood circulation and cardioplegia. Results and discussion. After the operation, the patient does not have shortness of breath, increased tolerance to physical exertion, end diastolic LV volume decreased from 430 to 212 ml, LVEF increased from 28 to 48%.Two months after the op-eration, the patient underwent a stress test-a treadmill test, in which the exercise tolerance was average, MET 5.4, during the test for signs of myocardial ischemia and cardiac arrhythmias were not observed. The developed technique at the National Institute of Cardiovascular Surgery named after NM Amosov, already at the hospital stage after surgery, allows to obtain improved LV contractility. The data of control echocardiography showed the effectiveness and reliability of the technique in restoring adequate LV cavity geometry, in many variants of left ventricle aneurysm to bring it closer to the natural form. Conclusions. The developed method, already at the hospital stage after the operation, shows a positive dynamics in the patient’s condition, allows to obtain improved parameters of the contractile function of the left ventricle, as evidenced by a significant increase in LVEF and a decrease in LV volumes.